Wadsworth and Putnam family papers - Putnam, Daniel, 1759-1831.; Wadsworth, Daniel, 1704-1747.; Wadsworth, Jeremiah, 1743-1804.
Correspondence and other papers of various members of the Wadsworth and Putnam families, especially Daniel Putnam, Daniel Wadsworth, and Jeremiah Wadsworth. Includes correspondence of Jeremiah Wadsworth while commissary general for the Continental Army relating to the problems of supplying the troops and the progress of the Revolutionary War in Connecticut, and letters of Daniel Putnam to George Brinley and Daniel Webster rebutting charges by Henry Dearborn that his father, Israel Putnam, had been guilty of cowardice at Bunker Hill. Other correspondents include Joel Barlow, George Clinton, Timothy Dwight, John Fitch, James Hillhouse, Samuel Holden Parsons, and Oliver Wolcott.
Photocopies.
Connecticut Historical Society
Members of the Wadsworth and Putnam families.
Collection material in English.
Inventory available in the Library of Congress Manuscript Reading Room.
Keywords: Barlow, Joel, -- 1754-1812 -- Correspondence; Brinley, George, -- -1857 -- Correspondence; Clinton, George, -- 1739-1812 -- Correspondence; Dearborn, Henry, -- 1751-1829.; Dwight, Timothy, -- 1752-1817 -- Correspondence; Fitch, John, -- 1743-1798 -- Correspondence; Hillhouse, James, -- 1754-1832 -- Correspondence; Parsons, Samuel Holden, -- 1737-1789 -- Correspondence; Putnam, Israel, -- 1718-1790.; Webster, Daniel, -- 1782-1852 -- Correspondence; Wolcott, Oliver, -- 1726-1797 -- Correspondence; Putnam family; Wadsworth family; United States. -- Continental Army -- Supplies and stores; Bunker Hill, Battle of, Boston, Mass., 1775.; Connecticut -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.